2014
DOI: 10.5194/bg-11-2571-2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water availability in the distributions of branched glycerol dialkyl glycerol tetraether in soils of the Iberian Peninsula

Abstract: Abstract. The combined application of the MBT (degree of methylation) and CBT (degree of cyclization) indices, based on the distribution of branched glycerol dialkyl glycerol tetraethers (brGDGTs) in soils, has been proposed as a paleoproxy to estimate mean annual temperature (MAT). CBT quantifies the degree of cyclization of brGDGTs and relates to soil pH. MBT and the simplified version MBT' quantify the degree of methylation of brGDGTs and relate to MAT and soil pH. However, other factors such as soil water … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 40 publications
4
47
2
Order By: Relevance
“…The decrease of MBT or MBT 0 with increasing elevation is, therefore, very likely associated with decreases of temperature and soil pH, which suggests that the MBT-or MBT 0 -CBT index may be valid for temperature estimation. The validity of MBT or MBT 0 as a temperature proxy in this arid area is different from previous findings (Peterse et al, 2012;Dirghangi et al, 2013;Menges et al, 2014), which might be associated with a strong monsoon climate. Summer monsoon accounts for 80% annual precipitation in the area, leading to relatively wet conditions in summer.…”
Section: Mbt and Mbtcontrasting
confidence: 99%
See 1 more Smart Citation
“…The decrease of MBT or MBT 0 with increasing elevation is, therefore, very likely associated with decreases of temperature and soil pH, which suggests that the MBT-or MBT 0 -CBT index may be valid for temperature estimation. The validity of MBT or MBT 0 as a temperature proxy in this arid area is different from previous findings (Peterse et al, 2012;Dirghangi et al, 2013;Menges et al, 2014), which might be associated with a strong monsoon climate. Summer monsoon accounts for 80% annual precipitation in the area, leading to relatively wet conditions in summer.…”
Section: Mbt and Mbtcontrasting
confidence: 99%
“…A number of studies have noted that the MBT or MBT 0 proxy showed no correlation with MAAT but significant correlation with MAP or aridity index in arid environments, e.g. in areas with MAP < 800 mm (Dirghangi et al, 2013;Menges et al, 2014). All the study sites here are in a relatively dry climate, with MAP generally < 500 mm as measured at nearby weather stations.…”
Section: Mbt and Mbtmentioning
confidence: 67%
“…The MAP at the sampling sites is indeed low at 450-910 mm yr −1 (Table 1). A recent study of 23 Iberian soils (Menges et al, 2014) has revealed similar variable MBT' and DC (or CBT) values to those we report here. In that study it is suggested that the MBT' is primarily related with the MAP and soil aridity.…”
Section: Gdgts In Soils Of the Tagus Drainage Basinsupporting
confidence: 88%
“…Indeed the pH of all but one of the soils studied were above 5.5. Recently, reduced values of the BIT index in soils have also been attributed to a dry climate Dirghangi et al, 2013;Menges et al, 2014). The reason for the low BIT could be that in dry soils, oxygen can penetrate further into the soil (Cleveland et al, 2010).…”
Section: Gdgts In Soils Of the Tagus Drainage Basinmentioning
confidence: 99%
“…We use the MBT' and DC to compare the brGDGT distribution in the different environments. The values of CL MBT' and DC of soils in the Tagus River basin (Zell et al, 2014a) and also in those of the whole Iberian Peninsula (Menges et al, 2014) vary widely. Compared to the average of the Tagus basin soils the CL MBT' and DC in the Tagus River were higher, which most likely means that brGDGTs are mainly produced in the Tagus River itself and are not derived from soil erosion (Zell et al, 2014a) (Fig.…”
Section: Provenance Of Brgdgts: Terrestrial Vs Marinementioning
confidence: 99%